CHALCOLITHIC CERAMIC CONNECTIONS BETWEEN MESOPOTAMIA AND IRAN, c.5900–5100 b.c.e. (4th October 2018) - Sharp, Melissa; Kaercher, Kyra
Abstract : The Chalcolithic period in Mesopotamia and Iran ( c. 6000–4000b.c.e. ) is characterised by larger cities replacing small farming settlements, technological developments including wheel thrown pottery and copper metal working, and people establishing long distance trade networks. The Halaf horizon (5900–5100b.c.e. ) developed out of the local late pottery Neolithic tradition and is found throughout western Syria, southern Turkey, and northern and central Iraq. This archaeological culture is defined by a finely painted pottery, dryland farming, round and rectangular houses, and the use of stamp seals. A comparable ceramic horizon, the J-ware horizon (5200–4700b.c.e. ) arose in the Mahidasht and Kermanshah valleys of Iran. The J-ware ceramics are finely painted, possibly deriving from the Halaf tradition, but also slipped and burnished. The Rowanduz Archaeological Program's (RAP) excavations elucidate links between northern Iraq and northern Iran from the Chalcolithic to the modern period. This paper explores the relationship between the Halaf and J-ware traditions at Banahilk, recently re-excavated by RAP, and the larger contacts during the Chalcolithic.